2012
DOI: 10.1098/rspb.2012.1621
|View full text |Cite
|
Sign up to set email alerts
|

Diverse pollinator communities enhance plant reproductive success

Abstract: Understanding the functional consequences of biodiversity loss is a major goal of ecology. Animal-mediated pollination is an essential ecosystem function and service provided to mankind. However, little is known how pollinator diversity could affect pollination services. Using a substitutive design, we experimentally manipulated functional group (FG) and species richness of pollinator communities to investigate their consequences on the reproductive success of an obligate out-crossing model plant species, Raph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
226
0
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 236 publications
(241 citation statements)
references
References 60 publications
(125 reference statements)
9
226
0
6
Order By: Relevance
“…Several floral visitors of one species of Tibouchina (T. pulchra), studied by Pereira et al (2011), belonged to three genera also found visiting P. trichopodum, and vary in their relative lengths (size). This trait variation could indicate a certain degree of functional complementarity and enhance the reproductive success of plant communities (Fontaine et al 2006;Albrecht et al 2012). The enhanced attractiveness of high floral display plants to different bees shows that these trees might function as islands of resources (Brito et al 2015) in areas where exotic herbs are dominant.…”
Section: Discussionmentioning
confidence: 99%
“…Several floral visitors of one species of Tibouchina (T. pulchra), studied by Pereira et al (2011), belonged to three genera also found visiting P. trichopodum, and vary in their relative lengths (size). This trait variation could indicate a certain degree of functional complementarity and enhance the reproductive success of plant communities (Fontaine et al 2006;Albrecht et al 2012). The enhanced attractiveness of high floral display plants to different bees shows that these trees might function as islands of resources (Brito et al 2015) in areas where exotic herbs are dominant.…”
Section: Discussionmentioning
confidence: 99%
“…The loss of a given pollinator functional group may impede reproduction of the wild and cultivated plants that depend on the pollinator group, although empirical studies are limited (e.g. [12][13][14][15][16]). …”
Section: Introductionmentioning
confidence: 99%
“…Blitzer et al (2016) found that functional diversity of bee pollinators explained more variation in apple pollination than species richness, arguably due to increased complementarity with increasing functional richness. Albrecht et al (2012) found that radish fruit and seed set increased with functional group diversity and with increased species richness within single functional group, suggesting the importance of both species specific effects and functional richness. In mesocosm experiments with wild flowers, Frund et al (2013), found that greater coverage of functional niche space predicted seed production better than species richness.…”
Section: Complementarity and Functional Diversitymentioning
confidence: 95%